Composite Perturbation-Rejection Trajectory-Tracking Control for a Quadrotor–Slung Load System - Jiao Xu; Defu Lin; Jianchuan Ye; Tao Jiang (Actuators)
Tracking control of a quadrotor–slung load system is extremely challenging due to its under-actuation property, couple effects, and various uncertainties. This work proposes a composite backstepping control framework combining command filter control and a multivariable finite-time disturbance observer to ensure robust position and orientation control for aerial payload transportation with high precision. Firstly, the kinematic and dynamic model under perturbations is derived based on Newton’s second law. The thrust control force consists of two orthogonal parts, each dedicated to regulating the position and orientation of the slung load independently. Then, hierarchical backstepping control generates the two parts in the load-translation and the load-orientation subsystems. Command filters are introduced into nonlinear backstepping to smoothen the control signals and overcome the problem of explosion of complexity. Additionally, to counteract the adverse effect of perturbations emerging in the linear velocity and angular velocity loops, multivariable finite-time observers are developed to ensure the estimation errors converge within a finite time horizon. Finally, comparative numerical simulation results validate the efficacy of the developed quadrotor–slung load tracking controller. Simulation results show that the proposed controller achieves smaller position tracking and orientation errors compared to traditional methods, demonstrating robust disturbance rejection and high-precision control.